2022
DOI: 10.1039/d2ra00071g
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-based nanocapsules for the controlled release of dietary curcumin: PDDA and silica nanoparticle-coated DMPC liposomes enhance the fluorescence efficiency and anticancer activity of curcumin

Abstract: Nanosystems with various compositions and biological properties are being extensively investigated for drug and gene delivery applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The absorption maximum of curcumin at 430 nm was shifted to 403 nm, and that of CP at 265 was shifted to 275 nm. The observed shift in curcumin absorption maximum may be due to the complex formation with PL, and the shift observed in CPs can be due to the variations in the microenvironment of the aromatic side chains. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption maximum of curcumin at 430 nm was shifted to 403 nm, and that of CP at 265 was shifted to 275 nm. The observed shift in curcumin absorption maximum may be due to the complex formation with PL, and the shift observed in CPs can be due to the variations in the microenvironment of the aromatic side chains. , …”
Section: Resultsmentioning
confidence: 99%
“…The absorption maximum of curcumin at 430 nm was shifted to 403 nm, and that of CP at 265 was shifted to 275 nm. The observed shift in curcumin absorption maximum may be due to the complex formation with PL, 31 and the shift observed in CPs can be due to the variations in the microenvironment of the aromatic side chains. 29,30 Fluorescence spectra of C95 and CCL were recorded at an excitation wavelength of 420 nm, and the corresponding emission was observed at 540 nm for C95 and at 527 nm for CCL (Figure 2e).…”
Section: Preparation and Characterizationmentioning
confidence: 99%
“…Free drugs releasing from L‐drugs could be regulated by liposome stability optimization. It has been found that liposome encapsulation could reduce toxicity and increase efficacy of drug through manipulating drugs release (mainly slow release) [11]. Simultaneous pharmacokinetic characterization of the free drugs and liposome‐encapsulating drugs in vivo was important for both liposomal drugs development and clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…19 Henceforth, PDDA polymer was proven by Othman et al, to be an effective polymer in increasing the stability of curcumin inside DMPC liposomes by decreasing thereby its release. 20 Dopamine is a catecholamine neurotransmitter in nervous, cardiovascular and hormonal systems, plays an important role as an extracellular chemical messenger. 21,22 Many diseases result from disorder in the level of dopamine.…”
Section: Introductionmentioning
confidence: 99%
“… 19 Henceforth, PDDA polymer was proven by Othman et al , to be an effective polymer in increasing the stability of curcumin inside DMPC liposomes by decreasing thereby its release. 20 …”
Section: Introductionmentioning
confidence: 99%